1994
DOI: 10.1002/1097-0142(19940101)73:1<15::aid-cncr2820730105>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic differences between carcinoma in the gastric remnant stump after distal partial gastrectomy for benign gastroduodenal lesions and primary carcinoma in the upper third of the stomach

Abstract: Background. This study evaluated the prognosis of patients with carcinoma in the gastric remnant stump after distal gastrectomy for benign disease (stump cancer). Methods. Twenty patients with resected stump cancer were studied and compared with 266 patients with resected primary cancer in the upper third of the stomach (primary cancer). Results. The percentages of lymph nodes with metastases located at the lesser curvature and the left gastric artery, respectively, were 50.0% and 25.2% in patients with primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…Thirty-eight studies were given an A score, and 68 studies were given a B score. Finally, we conducted a publication-based meta-analysis using 20 studies that compared the 5-year survival rates between RGC and PGC [3,6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In addition, eight studies included data on TNM staging along with the survival data [3,6,13,14,16,17,23,29].…”
Section: Studies Included In the Present Articlementioning
confidence: 99%
See 2 more Smart Citations
“…Thirty-eight studies were given an A score, and 68 studies were given a B score. Finally, we conducted a publication-based meta-analysis using 20 studies that compared the 5-year survival rates between RGC and PGC [3,6,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In addition, eight studies included data on TNM staging along with the survival data [3,6,13,14,16,17,23,29].…”
Section: Studies Included In the Present Articlementioning
confidence: 99%
“…Lymph node involvement in the jejunal mesentery is a phenomenon peculiar to the RGC after Billroth II reconstruction, with the reported incidence ranging from 7.0 % to 46.8 % [3,6,14,15,26,[51][52][53][54][55][56] (Table 4). Several authors have reported relatively high incidences of lymph node metastases at the splenic hilum in patients with RGC [15,50,51,55].…”
Section: Molecular Carcinogenesis Of Rgcmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, most studies of lymphatic flow have investigated group B patients. Indeed, no previous study has reported the changes in lymphatic flow in patients in group M, or the optimal range for lymph node dissection [4,8,9]. This study aimed to compare the regions of lymph node metastases and lymphatic flow between cases in group B and in group M.…”
Section: Introductionmentioning
confidence: 95%
“…In cases of CRS, it appears that changes in lymphatic flow can occur as consequences of lymph node dissection, vascular dissection, anastomosis, and gastrointestinal adhesions from the initial surgery [8,9]. For example, metastasis to the mesojejunal lymph nodes has been reported after Billroth II (B-II) reconstruction, and changes to lymphatic flow due to gastrointestinal anastomosis have been observed [4,10].…”
Section: Introductionmentioning
confidence: 99%